2017
DOI: 10.1039/c7ra02264f
|View full text |Cite
|
Sign up to set email alerts
|

Directly grown carbon nanotube based hybrid electrodes with enhanced thermo-cell performances

Abstract: Hybrid electrodes exhibit intriguing properties due to the synergetic effect of different components that are propitious for the practical applications of thermo-cells (TECs). In this study, Ag-carbon nanotube (CNT) hybrid electrodes were prepared using two simple and effective steps, involving the direct growth of CNTs on stainless steel substrates without any external catalyst, followed by decorating the CNTs with Ag nanoparticles. Ag-CNT electrodes were characterized via scanning electron microscopy, X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…Im et al reported that the CNT-Pt hybrid nanostructure could achieve much higher conversation efficiency in comparison with the pristine CNTs for the faster kinetics and larger electroactive sites [12]. Our investigation showed that CNT-Ag hybrids exhibited better TEC performances due to higher electric and thermal conductivities, as well as more activation sites [11]. Romano et al reported that the TEC performances of single-walled CNT-reduced graphene oxide hybrid electrodes were improved significantly compared to the pristine CNT sample, due to the enhancement of the mass transport property [13].…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…Im et al reported that the CNT-Pt hybrid nanostructure could achieve much higher conversation efficiency in comparison with the pristine CNTs for the faster kinetics and larger electroactive sites [12]. Our investigation showed that CNT-Ag hybrids exhibited better TEC performances due to higher electric and thermal conductivities, as well as more activation sites [11]. Romano et al reported that the TEC performances of single-walled CNT-reduced graphene oxide hybrid electrodes were improved significantly compared to the pristine CNT sample, due to the enhancement of the mass transport property [13].…”
Section: Introductionmentioning
confidence: 64%
“…XRD and Raman characterizations were applied to check the compositions of the products, as shown in Figure 3. XRD result (Figure 3a) indicates that the peak at 26.4° belongs to (002) crystallographic planes of CNT [10,11,23], and other four peaks should be attributed to the (111), (110), (200), and (220) planes of the stainless steel substrate, respectively [10,11]. As shown in Figure 3b, the Raman spectrum shows three typical characteristic peaks of the CNTs, i.e., D band (1350 cm −1 ), G band (1585 cm −1 ), and G’ (2706 cm −1 ), respectively [11,24].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations